Giving an Individual Tutoring for 8th Grade Student in the Errors of Solving the Problem of Essay Test for Comparative Material in SMPN 232 Jakarta - Yusufira Aldona; Pinta Deniyanti Sampoerno; Lukman El Hakim; Dwi Antari Wijayanti (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
This study aims to describe students’ errors in solving the problem of essay test for comparative material based on the type of errors, describe the causes of students making errors, and conduct individual tutoring to minimize and overcome students’ errors. This is action research that conducted in three cycles with Research Subject (RS) for four students of class VIII F SMPN 232 Jakarta. Each RS represents one type of error based on the results of error analysis on initial test that given during pre-cycle, successive factual error, conceptual error, operation error, and principle of error. The instruments used in this study were initial test, end-cycle tests, documentation tools, interview guidelines, tutor guidelines, observation sheets, and field notes. The data was analyzed qualitatively. The results showed that in cycle I, RS1 still made a factual error, RS2 also made a conceptual error, while RS3 and RS4 had not made any errors. In cycle II and III, RS1, RS2, RS3, and RS4 had not made any errors. The cause of the factual error is lack of thoroughness. The cause of the conceptual error is not understanding the concept of the comparison type. The cause of the operation error is lack of thoroughness and haste. The cause of the principle of error is lack of thoroughness. It can be concluded that individual tutoring can minimize and overcome students’ errors in solving the problem of essay test for comparative material. Keywords: students’ error, essay test, individual tutoring, comparative material.